Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm trying to show that $$ u_{n}=\sum_{k=1}^n (-1)^k\sqrt{k}\sim_{n\rightarrow \infty} (-1)^n\frac{\sqrt{n}}{2}$$ when $n\rightarrow\infty$

How can I first show that $$u_{2n}\sim_{n\rightarrow \infty} \frac{\sqrt{2n}}{2}$$ and then deduce the equivalent of $u_{n}$?

share|cite|improve this question
You can simply swap $2n$ with $n$ both in the formula and the index to deduce the equivalent. – Pedro Tamaroff Jun 7 '12 at 18:04
up vote 3 down vote accepted

Pair consecutive terms together:

$$u_{2n} = \sum_{k=1}^{2n} (-1)^k \sqrt{k} = \sum_{k=1}^n \left( \sqrt{2k}-\sqrt{2k-1}\right) .$$

Since $\displaystyle \sqrt{1 - \frac{1}{2k}} = 1 - \frac{1}{4k} + \mathcal{O}(k^{-2})$ and $\displaystyle \sum_{k=1}^n k^p = \frac{n^{p+1}}{p+1} + \frac{n^p}{2} + \mathcal{O}(n^{p-1})$ we get

$$u_{2n}= \sum_{k=1}^n \left(\frac{\sqrt{2}}{4\sqrt{k}} + \mathcal{O}(k^{-3/2})\right)= \frac{\sqrt{2n}}{2} + \mathcal{O}(1).$$

Now $u_{2n+1} = u_{2n} - \sqrt{2n+1}$ so the result that actually holds is $\displaystyle u_n \sim (-1)^n \frac{\sqrt{n}}{2}.$

share|cite|improve this answer
You cannot say $\sum_{k=1}^n O(k^{-3/2}) = O(n^{-1/2})$ ... it could be as bad as $O(1)$. – GEdgar Jun 7 '12 at 18:43
@GEdgar Ahh yes, sorry. I'll fix that now. – Ragib Zaman Jun 7 '12 at 18:46
@Ragib Zaman: I got it thank you very much for your answer! – Chon Jun 7 '12 at 19:05

We have estimations $$ u_{2n}=\sum\limits_{k=1}^{2n}(-1)^k\sqrt{k}= \sum\limits_{k=1}^{n}(\sqrt{2k}-\sqrt{2k-1})= \sum\limits_{k=1}^{n}\frac{1}{\sqrt{2k}+\sqrt{2k-1}}\leq $$ $$ \sum\limits_{k=1}^{n}\frac{1}{2\sqrt{2k-1}}\leq \int\limits_{1}^n\frac{dx}{2\sqrt{2(x+1)-1}}=\frac{\sqrt{2n+1}-\sqrt{3}}{2} $$ and $$ u_{2n}=\sum\limits_{k=1}^{2n}(-1)^k\sqrt{k}= \sum\limits_{k=1}^{n}(\sqrt{2k}-\sqrt{2k-1})= \sum\limits_{k=1}^{n}\frac{1}{\sqrt{2k}+\sqrt{2k-1}}\geq $$ $$ \sum\limits_{k=1}^{n}\frac{1}{2\sqrt{2k}}\geq \int\limits_{1}^n\frac{dx}{2\sqrt{2x}}=\frac{\sqrt{2n}-\sqrt{2}}{2} $$ hence $u_{2n}\sim\frac{1}{2}\sqrt{2n}$ while $n\to\infty$.

share|cite|improve this answer
Thank you very much Norbert! – Chon Jun 7 '12 at 19:06
@Chone, you are welcome! – Norbert Jun 7 '12 at 19:11

Norbert's answer is the simplest with the fewest prerequisites. That being the case, here is a nuke for an ant hill using the Euler-Maclaurin Sum Formula.

Note that $$ \begin{align} \sum_{k=1}^{2n}(-1)^k\sqrt{k} &=2\sum_{k=1}^{n}\sqrt{2k}\;-\;\sum_{k=1}^{2n}\sqrt{k}\\ &=\sqrt{8}\sum_{k=1}^{n}\sqrt{k}\;-\;\sum_{k=1}^{2n}\sqrt{k}\tag{1} \end{align} $$ The Euler-Maclaurin Sum Formula says that $$ \sum_{k=1}^n\sqrt{k}=\frac23n^{3/2}+\frac12n^{1/2}+C+\frac{1}{24}n^{-1/2}+O\left(n^{-3/2}\right)\tag{2} $$ For $\mathrm{Re}(z)>-1$, $$ \zeta(z)=\lim_{n\to\infty}\sum_{k=1}^nk^{-z}\;-\;\left(\frac{1}{1-z}n^{1-z}+\frac12n^{-z}\right)\tag{3} $$ Applying $(3)$ to $(2)$ yields $C=\zeta(-\frac12)=-\frac{1}{4\pi}\zeta(\frac32)\,\dot{=}-0.207886224977354566$.

Applying $(2)$ to $(1)$ yields $$ \begin{align} \sum_{k=1}^{2n}(-1)^k\sqrt{k} &=\sqrt{8}\sum_{k=1}^{n}\sqrt{k}\;-\;\sum_{k=1}^{2n}\sqrt{k}\\ &=\sqrt{8}\left(\frac23n^{3/2}+\frac12n^{1/2}+C+\frac{1}{24}n^{-1/2}\right)\\ &-\left(\sqrt{8}\frac23n^{3/2}+\sqrt2{}\frac12n^{1/2}+C+\frac{1}{\sqrt{2}}\frac{1}{24}n^{-1/2}\right)+O\left(n^{-3/2}\right)\\ &=\frac{1}{\sqrt{2}}n^{1/2}+(\sqrt{8}-1)C+\frac{3}{\sqrt{2}}\frac{1}{24}n^{-1/2}+O\left(n^{-3/2}\right)\tag{4} \end{align} $$ Thus, for even $n$, we get $$ \sum_{k=1}^{n}(-1)^k\sqrt{k}=\frac12n^{1/2}+\frac18n^{-1/2}+\frac{7C}{\sqrt{8}+1}+O\left(n^{-3/2}\right)\tag{5} $$ For odd $n$, we get $$ \begin{align} \sum_{k=1}^{n}(-1)^k\sqrt{k} &=\sum_{k=1}^{n-1}(-1)^k\sqrt{k}\;-\;\sqrt{n}\\ &=\color{red}{\frac12(n-1)^{1/2}}+\color{green}{\frac18(n-1)^{-1/2}}-n^{1/2}+\frac{7C}{\sqrt{8}+1}+O\left(n^{-3/2}\right)\\ &=\color{red}{\frac12n^{1/2}-\frac14n^{-1/2}}+\color{green}{\frac18n^{-1/2}}-n^{1/2}+\frac{7C}{\sqrt{8}+1}+O\left(n^{-3/2}\right)\\ &=-\frac12n^{1/2}-\frac18n^{-1/2}+\frac{7C}{\sqrt{8}+1}+O\left(n^{-3/2}\right)\tag{6} \end{align} $$ using the $\color{red}{\text{Binomial}}$ $\color{green}{\text{Theorem}}$ to expand the powers of $(n-1)$ to $O\left(n^{-3/2}\right)$.

Combining $(5)$ and $(6)$, we get $$ \sum_{k=1}^{n}(-1)^k\sqrt{k}=(-1)^n\left(\frac12n^{1/2}+\frac18n^{-1/2}\right)-\frac{7}{\sqrt{8}+1}\frac{\zeta(\frac32)}{4\pi}+O\left(n^{-3/2}\right)\tag{7} $$ We've used more powerful machinery, but we've also gotten a more precise answer.

share|cite|improve this answer
Thank you for this detailed answer! – Chon Jun 7 '12 at 19:44
@Chon: I've expanded the answer to use more terms of the Euler-Maclaurin Sum Formula. This reveals the usefulness of that formula. – robjohn Jun 7 '12 at 20:00

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.